STRATEGI KONTRA RADIKALISME KEAGAMAAN NAHDLATUL ULAMA DI DESA JAMBON, KECAMATAN GEMAWANG KABUPATEN TEMANGGUNG - Khamim Saifuddin (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
The emergence of Islamic organization groups outside Nahdlatul Ulama and Muhammadiyah in Jambon, Gemawang, Temanggung has an impact to society’s religiosity. The religious activities of those Islamic groups tend to be radical and different with the existed other Islamic groups. NU as a representation of Islam Nusantara is known to be tolerant, moderate and accommodative to culture, tradition and all the differences. While radical Islam promotes againts religious traditions. This article aims at describing the NU’s strategy in stemming religious radicalism. The method used is qualitative descriptive and data is collected by interviews and field observations. The results of this study suggested that to counter radicalism, the NU branch in that region has built mechanism of massive and structured campaign, set da'wah materials using scientific approach, accompanied youth activities intensively. Such efforts become resposibility for all components of society in order to become a stronghold of the influence of radical Islamic ideology, especially among the younger generation. The indicator can be seen in the increasing quantity of students in non-formal and formal educational institutions in Jambon, which is quite significant. Besides, public awareness appears to be selective in choosing incoming Islamic teachings.